More than One Way to be Happy: A Typology of Marital Happiness. Issue 3 (2nd April 2013) - Rauer, Amy; Volling, Brenda
<x xml:space="preserve">Abstract</x> This study utilized observational and self‐report data from 57 happily married couples to explore assumptions regarding marital happiness. Suggesting that happily married couples are not a homogeneous group, cluster analyses revealed the existence of three types of couples based on their observed behaviors in a problem‐solving task: (1) mutually engaged couples (characterized by both spouses' higher negative and positive problem‐solving); (2) mutually supportive couples (characterized by both spouses' higher positivity and support); and (3) wife compensation couples (characterized by high wife positivity). Although couples in all three clusters were equally happy with and committed to their marriages, these clusters were differentially associated with spouses' evaluations of their marriage. Spouses in the mutually supportive cluster reported greater intimacy and maintenance and less conflict and ambivalence, although this was more consistently the case in comparison to the wife compensation cluster, as opposed to the mutually engaged cluster. The implications of these typologies are discussed as they pertain to efforts on the part of both practitioners to promote marital happiness and repair marital relations when couples are faced with difficulties.